Poetry of Amjad Islam Amjad - Sadaf Naqvi (بازیافت)
Amjad Islam Amjad is a renowned poet. He holds proficiency in both Poem and Ghazal. He has portrayed every topic of the universe in his poetry. We find delicate musical sense in his poetry. The epic of emotions, attachment with classic and innovation has made him a unique poet.